(untitled) (International Journal of Language, Literacy and Translation, 2025)
One crucial effect of technological advancement is evident in the powerful increase in the production and worldwide movement of audiovisual materials, thus promoting wide scale access and consumption of telecinematic products for education, entertainment, leisure, as well as information gathering. On a related note, Audiovisual Translation (AVT) field has emerged into a mature field of research in Translation Studies, revealing rapid increase in the audiovisual content flow in different forms with comprehensive, descriptive and scientific approaches. The goal of this paper is to look into the depiction of Malay artistic treasures in a foreign setting. In addition to this, the paper analyzes the way the English subtitle of “Keris Siamang Tunggal” depicts each of the Malay cultural items in “Keris Siamang Tunggal”. In this study, the author tested one of the successful Malaysia’s animated films “Keris Siamang Tunggal” which has tremendously portrayed unique and historical Malay cultural items - Malay folklores iconic figures, royal language, and other Malay cultural items such as traditional weapons, literature, performing arts, classical words, slangs, forms of address, and food identity - by means of English subtitles and visuals/images. This local animated film was chosen for the discussion, while Katan’s (2009) and Schwarz’s (2002) guide on cultural items translation with regards to the classification of cultural items and the translation of the items in the context of audiovisual medium, were selected to build the basis of the investigation and steer this descriptive-based study. Katan’s theory classifies etymology and types of cultural items, while Schwarz’s theory seems to be useful, given that she focuses on cultural concept in films and that she relates them to the ones that appear on the screen. The result demonstrated that Keris Siamang Tunggal has portrayed 30 Malay cultural items, consisting of Malay folklores iconic figures, royal language and other Malay cultural items that covered traditional weapon, literature, performing arts, classical words, slang, forms of address, as well as food identity. From the 30 items, seven (7) were the iconic figures adapted from Malay traditional folklores, six (6) were the royal language, and 17 were other cultural items. This paper came to the vital conclusion that Keris Siamang Tunggal played a significant role in helping to shape and solidify Malay artistic treasures to the eye of western world, thus opening foreign audience’s eyes to new ways of thinking, feeling and pursuing Malay culture.